Editorial - Soares, Adriana Benevides; Tsallis, Alexandra Cleopatre; Mendes, Deise Maria Fernandes; Valentim, Renata Patrícia Forain de (Estudos e Pesquisas em Psicologia, 2018)
Adriana Benevides Soares, Alexandra Cleopatre Tsallis, Deise Maria Fernandes Mendes, Renata Patrícia Forain de Valentim